A Scoping Review of Audiovisual Integration Methodology: Screening for Auditory and Visual Impairment in Younger and Older Adults - Basharat, Aysha; Thayanithy, Archana; Barnett-Cowan, Michael (Frontiers in Aging Neuroscience, 2022)
With the rise of the aging population, many scientists studying multisensory integration have turned toward understanding how this process may change with age. This scoping review was conducted to understand and describe the scope and rigor with which researchers studying audiovisual sensory integration screen for hearing and vision impairment. A structured search in three licensed databases (Scopus, PubMed, and PsychInfo) using the key concepts of multisensory integration, audiovisual modality, and aging revealed 2,462 articles, which were screened for inclusion by two reviewers. Articles were included if they (1) tested healthy older adults (minimum mean or median age of 60) with younger adults as a comparison (mean or median age between 18 and 35), (2) measured auditory and visual integration, (3) were written in English, and (4) reported behavioral outcomes. Articles that included the following were excluded: (1) tested taste exclusively, (2) tested olfaction exclusively, (3) tested somatosensation exclusively, (4) tested emotion perception, (5) were not written in English, (6) were clinical commentaries, editorials, interviews, letters, newspaper articles, abstracts only, or non-peer reviewed literature (e.g., theses), and (7) focused on neuroimaging without a behavioral component. Data pertaining to the details of the study (e.g., country of publication, year of publication, etc.) were extracted, however, of higher importance to our research question, data pertaining to screening measures used for hearing and vision impairment (e.g., type of test used, whether hearing- and visual-aids were worn, thresholds used, etc.) were extracted, collated, and summarized. Our search revealed that only 64% of studies screened for age-abnormal hearing impairment, 51% screened for age-abnormal vision impairment, and that consistent definitions of normal or abnormal vision and hearing were not used among the studies that screened for sensory abilities. A total of 1,624 younger adults and 4,778 older participants were included in the scoping review with males composing approximately 44% and females composing 56% of the total sample and most of the data was obtained from only four countries. We recommend that studies investigating the effects of aging on multisensory integration should screen for normal vision and hearing by using the World Health Organization's (WHO) hearing loss and visual impairment cut-off scores in order to maintain consistency among other aging researchers. As mild cognitive impairment (MCI) has been defined as a “transitional” or a “transitory” stage between normal aging and dementia and because approximately 3–5% of the aging population will develop MCI each year, it is therefore important that when researchers aim to study a healthy aging population, that they appropriately screen for MCI. One of our secondary aims was to determine how often researchers were screening for cognitive impairment and the types of tests that were used to do so. Our results revealed that only 55 out of 72 studies tested for neurological and cognitive function, and only a subset used standardized tests. Additionally, among the studies that used standardized tests, the cut-off scores used were not always adequate for screening out mild cognitive impairment. An additional secondary aim of this scoping review was to determine the feasibility of whether a meta-analysis could be conducted in the future to further quantitatively evaluate the results (i.e., are the findings obtained from studies using self-reported vision and hearing impairment screening methods significantly different from those measuring vision and hearing impairment in the lab) and to assess the scope of this problem. We found that it may not be feasible to conduct a meta-analysis with the entire dataset of this scoping review. However, a meta-analysis can be conducted if stricter parameters are used (e.g., focusing on accuracy or response time data only). Systematic Review Registration:https://doi.org/10.17605/OSF.IO/GTUHD.